Thermal analysis of multistage solar distiller - Queh, Zhi Xian (2021)
Fresh water is essential as it is the basic need of biological processes. The demand for fresh water also increases steadily as the global population increases. There are multiple types of desalination processes such as reverse osmosis process, freezing process, ion-exchange process, thermal process and etcetera. Solar distiller is one of the oldest desalination processes that works based on two scientific principles, evaporation and condensation. This research uses theoretical analysis to estimate the distillate output and thermal performance of multistage solar distillers with different number of stages. It was found that the efficiency of solar distiller improves as the number of stages increases, 5-stages solar distiller was found to be the optimal number of stage, as any further increment in number of stage will lead to insignificant improvement in efficiency (< 1.5%). The distillate output also followed the same pattern and reached an optimal number at 5-stages solar distiller. Cost analysis was also done and it was found that 4-stages solar distiller was the optimal selection with the least cost per litre distillate output of RM 0.261/L.